Randomised, pragmatic, waitlist controlled trial of cannabis added to prescription opioid support on opioid dose reduction and pain in adults with chronic non-cancer pain: study protocol - A Eden Evins; Ellie Grossman; Julia Jashinski; Aurora Quaye; Corinne Cather; Kevin Potter; David A Schoenfeld; Jodi M Gilman (BMJ Open)
Introduction Chronic, non-cancer pain impacts approximately 50 million adults in the USA (20%), approximately 25% of whom receive chronic prescription opioids for pain despite limited empirical efficacy data and strong dose-related risk for opioid use disorder and opioid overdose. Also despite lack of efficacy data, there are many reports of people using cannabis products to manage chronic pain and replace or reduce chronic opioids. Here we describe the protocol for a randomised trial of the effect of cannabis, when added to a behavioural pain management and prescription opioid taper support programme, on opioid utilisation, pain intensity and pain interference.Methods This is a pragmatic, single-blind, randomised, wait-list controlled trial that aims to enrol 250 adults taking prescription opioids at stable doses of ≥25 morphine milligram equivalents per day for chronic non-cancer pain who express interest in using cannabis to reduce their pain, their opioid dose or both. All participants will be offered a weekly, 24-session Prescription Opioid Taper Support group behavioural pain management intervention. Participants will be randomly assigned in 1:1 ratio to use cannabis products, primarily from commercial cannabis dispensaries or to abstain from cannabis use for 6 months. Coprimary outcomes are change in prescription monitoring programme-verified opioid dose and change in Pain, Enjoyment, General Activity scale scores. Secondary outcomes include quality of life, depression, anxiety, self-reported opioid dose and opioid and cannabis use disorder symptoms. All other outcomes will be exploratory. We will record adverse events.Ethics and dissemination This study has ethical approval by the Massachusetts General Brigham Institutional Review Board (#2021P000871). Results will be published in peer-reviewed journals and presented at national conferences.Trial registration number NCT04827992.